Tafsir terhadap Dasar-dasar Ideologi TakfÃ„Â«r Kelompok Islam Radikal - Hanafi, Muchlis Muhammad (SUHUF, 2014)
In the last two decades, there are many violences done by the radical moslem groups, such as Al-Qaedah, Jamaah Islamiyah, and in the last two months, Islamic State of Iraq and Syam (ISIS) toward people or other Moslems groups, institutions, and government. Using the argument that they want to stand with the Islamic roles and to create political entity in the form of a single leadership (khalÃ„Â«fah), they do everything they can in the name of religion. In fact, almost all religions including Islam, teach their followers to spread the love (rahmatan li al-Ã¢â‚¬ËœÃ„ÂlamÃ„Â«n) and love peace. Through a content analysis approach (content analysis) against the number of written documents, and against the Muslims groups causing violence, this paper will reveal their ideological foundations underlying attitude of the hatred toward other Muslim people. Furthermore, this writing will analyze their interpretation using thematic interpretatation method (mawdÃ…Â«Ã¢â‚¬Ëœiy) by means of collecting religious texts (verses and hadith) and analyzing them to be an integrated parts. This religious study is also expected to reveal the basics of their radical ideology known as Ã¢â‚¬Å“ hatred groupsÃ¢â‚¬Â which eventually lead to the act of violence. It is worth noting that to accuse Muslims of being infidels or apostates is not easy. Keywords: Islamic radicalism, takfÃ„Â«r, murtad (apostate), violance